2019
DOI: 10.1038/s41430-018-0380-y
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the incidence of postoperative pneumonia after percutaneous endoscopic gastrostomy between liquid and semi-solid nutrient administration

Abstract: Background/ObjectivesThis historical control study examined the differences in the incidence of postoperative pneumonia between patients administered liquid and semi-solid nutrients after percutaneous endoscopic gastrostomy (PEG).Subjects/MethodsThe medical records of adult patients who underwent PEG between March 1999 and March 2014 were investigated. The patients were administered either liquid or semi-solid nutrient and examined for gastroesophageal reflux via radiography after PEG. The study period was div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Moreover, previous studies used a variety of semisolid nutrient preparations, with viscosities ranging from 1000 to 20,000 mPas. [8][9][10]15,19,20 To date, neither viscosity of semisolid nutrient preparations nor methods for measuring that viscosity have been defined. 6,7 Therefore, differences in physical characteristics of different types of semisolid nutrient preparations may have resulted in inconsistency in study results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous studies used a variety of semisolid nutrient preparations, with viscosities ranging from 1000 to 20,000 mPas. [8][9][10]15,19,20 To date, neither viscosity of semisolid nutrient preparations nor methods for measuring that viscosity have been defined. 6,7 Therefore, differences in physical characteristics of different types of semisolid nutrient preparations may have resulted in inconsistency in study results.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that a smaller proportion of patients receiving semisolid nutrients than of those receiving liquid nutrients required readmission within 30 days after discharge 9 . However, no differences between semisolid and liquid nutrients in length of stay in intensive care units (ICUs) 12‐14 or short‐term mortality 9,12,15 have been reported. Additionally, studies have shown conflicting findings on the ability of semisolid nutrients to reduce vomiting, 8,12,14 pneumonia or lung infection, 8,9,12‐15 high blood glucose, 12,16 gastroesophageal reflux, 10,17‐19 diarrhea, 5,8‐10,14,20 fever, 8,20 length of hospital stay, 9,12,14 and peristomal infection 9,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Benefits of semi-solid nutrients such as reduced diarrhea, gastroesophageal reflux, and aspiration pneumonia were reported in some articles [[1], [2], [3]]. Most published articles focused on semi-solid nutrients through PEG.…”
Section: Discussionmentioning
confidence: 99%
“…They are useful for patients with diarrhea or reflux from enteral feeding. There are some reports insisting the safety and benefits of semi-solid nutrients such as reduced diarrhea, shorter administration time, and lower frequency of aspiration pneumonia [[1], [2], [3]]. Semi-solid nutrients are usually given through percutaneous endoscopic gastrostomy (PEG), but it is unsuitable for nasogastric tube administration due to its high viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…6 Semi-solid medical foods may reduce the risk of aspiration pneumonia in gastrostomy-fed patients. 12,13 My department will be conducting further investigation involving more patients receiving semisolid medical foods.…”
Section: Variablesmentioning
confidence: 99%